A formação docente: uma das atribuições do professor coordenador na escola - Pereira, Regiane Taveira (2017)
The object of the research is the pedagogical coordinator's as expert instructional and pedagogical support of the teachers in locus. The aim to analyze from the perspective of the teacher the intervention in the pedagogical practice from the formations realized in the classes of collective pedagogical work (ATPC). As a specific objective, we point out the following: to verify if the formations carried out by the pedagogical coordinator promoted means to innovate the practices in the classroom. We seek to answer the following questions: How is the training of this professional in the graduation in Pedagogy? Who is the pedagogical coordinator these days? Can your action contribute to the teachinglearning process of teachers and students? The research universe is a state public school located in the south zone of the city of São Paulo that serves children from 6 to 11 years. The members of this research will be teachers who participated in the ATPCs in the year 2016. The qualitative methodology is based on the data collection, obtained in semi-structured interviews and in dialogical actions developed in the formations in the hours of Pedagogical Work. Documents such as: the legislation governing the role of the pedagogical coordinator in primary education (cycle I) of the Secretariat of Education of the State of São Paulo, the curricular curricula of three higher education institutions, focusing on the training of the pedagogical coordinator, legislation Which governs the Basic Education Teaching, Directives and Bases of National Education Act 1996, PNE - National Education Plan (2014/2024). The analysis was processed from the records collected in the formations held and with interview. The references are based on the contributions of Paulo Freire (1996, 2001, 2005, 2013). The secondary references came from scholars of educational topics focusing on teacher training: Pedro Demo (1995; 1997; 2015), Libânio (2001; 2010) and Ferreira.